Student and School-level Predictors of Pharmacy Residency Attainment - Lyons, Kayley (Am J Pharm Educ, 2018)
Objective. To identify student and school level predictors of pharmacy residency attainment. Methods. Data were collected from the American Association of Colleges of Pharmacy (AACP) and the Carnegie Classification of Institutions of Higher Education. Logistic multilevel modeling was used to examine the effects of select student and school level characteristics on pharmacy residency attainment, as indicated by students on the AACP Graduating Student Survey (GSS) from 2013 to 2015. Results. The dataset included 24,351 graduating pharmacy students from 101 schools and colleges of pharmacy. Predictors of residency attainment included working in an institutional pharmacy, female gender, student age, school age, and Research I classification. Nonsignificant variables included curriculum type, class size, and institutional control. Conclusion. Student and pharmacy school characteristics impact the likelihood of pharmacy residency attainment. Further research is needed to understand the mechanisms associated with these effects.